2021
DOI: 10.1186/s12876-021-01611-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel hemostatic adhesive powder in patients with upper gastrointestinal tumor bleeding

Abstract: Background Gastrointestinal tumor bleeding remains a clinical challenge because it is difficult to treat with conventional endoscopic hemostatic options. Recently, an endoscopic hemostatic powder (UI-EWD) was developed and reported to provide effective control of upper gastrointestinal bleeding. The aim of current study was to evaluate the feasibility and efficacy of this novel hemostatic powder in tumor bleeding. Methods A total of 41 consecutive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…Shin et al studied UI-EWD use as monotherapy or rescue in 41 patients with malignant bleeding, including carcinoma, gastrointestinal stromal tumor, and lymphoma. Immediate hemostasis rate was high at 97.5 % and rebleeding rate was 22.5 % in 28 days 76 .…”
Section: Resultsmentioning
confidence: 90%
“…Shin et al studied UI-EWD use as monotherapy or rescue in 41 patients with malignant bleeding, including carcinoma, gastrointestinal stromal tumor, and lymphoma. Immediate hemostasis rate was high at 97.5 % and rebleeding rate was 22.5 % in 28 days 76 .…”
Section: Resultsmentioning
confidence: 90%
“…A cohort of 41 patients with GI tumor bleeding treated with TC-325 achieved immediate hemostasis in 97.5% and 28 days rebleeding in 22.5%. [11] A retrospective study including 12 patients with gastric malignant bleeding treated with a similar hemostatic powder reported immediate hemostasis in all patients and rebleeding in 16% [12]. A systematic review and meta-analysis including 11 prospective studies and 4 randomized trials found an immediate hemostasis rate of 93% with TC-325 powder (95% CI 90.3-95%, p < 0.001) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al conducted a randomized pilot trial comparing TC-325 with a standard of care (SOC) group, achieving immediate hemostasis in 90 % of patients treated with TC-325 versus 40 % in the SOC group ( P = 0.057) 4 . A cohort of 41 patients with gastrointestinal tumor bleeding treated with TC-325 achieved immediate hemostasis in 97.5 % and 28 days rebleeding in 22.5 % 11 . A retrospective study including 12 patients with gastric malignant bleeding treated with a similar hemostatic powder reported immediate hemostasis in all patients and rebleeding in 16 % 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 20 ] reported its use in five patients with tumoral GI bleeding and found that all experienced immediate bleeding control, and only one case had rebleeding. Shin et al [ 21 ] also reported immediate bleeding control in all patients with the use of the hemostatic powder in a study with 41 consecutive patients with tumoral UGIB. Although a hemostatic powder seems to be a safe and reliable option for hemostasis of tumoral bleeding, it was not available yet in our institution during the period of this study.…”
Section: Discussionmentioning
confidence: 99%